Analyzing heterogeneous effects: How competition by informal firms affects firms’ productivity in Nicaragua (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2024)
Using data from the World Bank’s 2010 and 2016 Enterprise Surveys, this research analyzed how informality affects the performance of Nicaraguan formal firms. Utilizing indices (IRICI) of informal competition intensity, significant variations were found between economic activities. The results indicate that factors such as firm size, never having been informal, capacity utilization, and location outside of Managua decrease the perception of threat. The intensity of informal competition appears to increase productivity in large firms, neutralize it in medium-sized firms, and decrease it in micro and small firms. Interactive factors with the investment climate showed that the time spent handling regulations and informal payments negatively affect productivity under high informal competition. Other factors, such as the time needed to obtain an import license, can have positive effects, allowing firms to differentiate themselves. Access to credit reduces the perception of threat and has positive but not significant effects on productivity, highlighting ongoing historical limitations. To improve the study, it is necessary to incorporate more aspects associated with the theorized benefits of formality. Although preventive measures were applied, empirically, the results should be validated using instrumental variables to obtain an IRICI index at the level of economic activities corrected for potential endogeneity.
Keywords: Enterprise Survey; IRICI Index; Informal Competition; Productivity; Investment Climate